Measurements of charged-particle multiplicity dependence of higher-order net-proton cumulants in p + p collisions at s=200 GeV from STAR at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2024)
We report on the charged-particle multiplicity dependence of net-proton cumulant ratios up to sixth order from s=200 GeV p+p collisions at the Relativistic Heavy Ion Collider (RHIC). The measured ratios C4/C2, C5/C1, and C6/C2 decrease with increased charged-particle multiplicity and rapidity acceptance. Neither the Skellam baselines nor PYTHIA8 calculations account for the observed multiplicity dependence. In addition, the ratios C5/C1 and C6/C2 approach negative values in the highest-multiplicity events, which implies that thermalized QCD matter may be formed in p+p collisions. © 2024 The Author(s)
Keywords: Crossover; Event-by-event fluctuation; Higher-order cumulant; QCD phase diagram; dept.phy; peer-reviewed